The Association Between Prediabetes and Dyslipidemia Among Attendants of Primary Care Health Centers in Jeddah, Saudi Arabia - Al Amri, Turki (Diabetes Metab Syndr Obes, 2019)
INTRODUCTION: Early detection and treatment of dysglycemia including diabetes and prediabetes is demonstrated to improve disease outcomes and prevent complications. OBJECTIVE: To assess the association of prediabetes with lipid metabolism disorders to clarify whether systematic screening for prediabetes should be proposed for individuals with dyslipidemia. MATERIAL AND METHODS: A cross-sectional study design, employing a stratified two-stage cluster sampling method recruited non-diabetic adults (age ≥18 years) from attendees of Primary Health Care (PHC) centers in Jeddah. Anthropomorphic measurements, demographic and clinical information were taken, and blood pressure was measured. Fasting blood sample was obtained for the measurement of plasma glucose (FPG), glycated hemoglobin (HbA1C), and lipid profile. Plasma glucose was estimated 1 hr after the ingestion of 50 g glucose (1h-OGTT). Prediabetes and dyslipidemia were defined according to international guidelines. Demographic and clinical factors of subjects with prediabetes, and those with normoglycemia were compared. Multiple logistic regression analysis was used to adjust for confounding factors. RESULTS: A total of 613 individuals were included with a mean age (±SD) of 32±11.8years, and 54.8% being female. Prediabetes was detected in 28.7%, and dyslipidemia in 54.2% of participants. After adjusting for age, an association was found for high low-density lipoprotein-cholesterol (LDL-C) and prediabetes based on any definition. After adjustment for body mass index (BMI), the association was retained for any type of dyslipidemia and in particular high LDL-C. After adjusting for both age and BMI, a significant association was found only between high LDL-C and prediabetes based on any definition (OR, 95% CI=1.50,1.02–2.19, P= 0.037). CONCLUSION: Even though high LDL-C is associated with an increased probability of prediabetes, a recommendation for universal screening of dyslipidemic patients requires further cohort studies.